Integrated Ecological Approach as Paradigm Shift towards Sustainability: Current Efforts and Challenges (Global Journal of Human-Social Science, 2018)
Currently ecosystem degradation is become the main challenges of human being. Conservation of resource and traditional restoration is not sufficient because of high consumption rate and limited resource left on the earth. Consequently, Ecological restoration become the prime option. It is scientific application of restoration ecology and deals with restoring the function, structure and process of ecosystem. It is holistic approach with the consideration of important factors of ecological, social, cultural, economic and policies. Though, different scholars attempt to describes integrated approach in Ecological restoration by combining different factors, still it is marginally addressed and successful practical implementation of ecological restoration also lack. This review aims to fill this gap by consider integrated ecological restoration as a paradigm shift to sustainability. This paper proposed a framework by reviewing and insight 118 scientific papers. The considered factors were scientific basis in restoration practice, flexible plan and management action, landscape perspective, socioeconomic and policy dimension, and Inter and Trans disciplinary approach. Integrated ecological restoration is a mechanism to address ecosystem resource degradation sustainably.
Keywords: ecology; ecosystem degradation; integrated ecological restoration; paradigm shift; sustainability